Workshop Internasional Youth PFA in the Campus Environment (Cyber Bulliying, Academic Crisis, and Student Safety) - Marwah Rusydiana; Amallia Putri; Dian Miranda; Halida; Yuline; Elli Yanti; Siti Natijatul Pu’at; Lukmanulhakim; Dias Khairina Sabila; Ariyani Ramadhani; Siska Perdina; Muhammad Saffuan Abdullah; Hishamudin Bin Salleh (Talenta Publisher, 2026)
The community service activity in the form of the International Workshop on Youth PFA in the Campus Environment (Cyberbullying, Academic Crisis, and Student Safety) was designed to strengthen students’ capacity in addressing psychological crises commonly encountered in higher education settings. This program involved 150 students from four universities in Pontianak and featured international speakers from Indonesia, Malaysia, Brunei Darussalam, and Jordan. All presented materials focused on managing academic crises, cyberbullying, student physical safety, and identity crises in the digital era through the framework of Psychological First Aid (PFA).The workshop was conducted in a hybrid format and encompassed interactive lectures, discussions, simulations, role-play activities, and hands-on PFA practice. Students gained a comprehensive understanding of emotional stabilization techniques, empathetic communication, early identification of distress indicators, and appropriate psychological referral procedures. The participants’ responses were highly positive, reflected through their strong enthusiasm, active engagement during discussions, and commitment to becoming PFA agents within their respective campus environments. This workshop not only enhanced students’ mental health literacy but also fostered collective awareness of the importance of cultivating a safe and supportive campus climate. Consequently, the activity has made a significant contribution to strengthening peer-support systems, improving student resilience, and promoting a campus culture that is attentive and responsive to psychological and safety-related issues faced by students.